Investment preferences and risk perception: Financial agents versus clients - Luisa Kling; Christian König-Kersting; Stefan T. Trautmann (University of Heidelberg, Department of Economics, 2019)
We study three fundamental components of financial agency settings: Perception and communication of investment profiles, the interaction of agents' and clients' preferences, and the role of (non-)monetary incentives. The perception of investment profile terminology is very heterogeneous, resulting in substantial miscommunication between clients and agents. Financial agents show a high willingness to implement their clients' preferred investment profiles independent of monetary incentives. Agents' investments for their clients are biased by their own investment preferences.
urn:nbn:de:bsz:16-heidok-273931
Keywords: D14; D83; G11; G21; 330; Decisions under risk; decisions of agents; risk perception; financial advice